Routledge Handbook of Development Ethics - Drydyk, Jay; Keleher, Lori (Taylor & Francis, 2019)
The Routledge Handbook of Development Ethics provides readers with insight into the central questions of development ethics, the main approaches to answering them, and areas for future research. Over the past seventy years, it has been argued and increasingly accepted that worthwhile development cannot be reduced to economic growth. Rather, a number of other goals must be realised: Enhancement of people's well-being Equitable sharing in benefits of development Empowerment to participate freely in development Environmental sustainability Promotion of human rights Promotion of cultural freedom, consistent with human rights Responsible conduct, including integrity over corruption Agreement that these are essential goals has also been accompanied by disagreements about how to conceptualize or apply them in different cases or contexts. Using these seven goals as an organizing principle, this handbook presents different approaches to achieving each one, drawing on academic literature, policy documents and practitioner experience. This international and multi-disciplinary handbook will be of great interest to development policy makers and program workers, students and scholars in development studies, public policy, international studies, applied ethics and other related disciplines.